2020
DOI: 10.22146/jieb.45652
|View full text |Cite
|
Sign up to set email alerts
|

Does Heuristic Behavior Leave Anomalies in the Capital Market?

Abstract: ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Individual investors often use recognition-based heuristics when trading in the stock market; they reduce the mental effort in the decision-making process, but that leads to errors in judgment and, as a result, anomalies persist in the market; due to these anomalies, investors make irrational investment decisions, and their investment performance was affected adversely. The findings are consistent with research by Lazuarni (2019) who found that heuristic biases are reasons for the existence of the technical and fundamental anomalies in the stock market, which negatively affect the investment performance of investors.…”
Section: Discussionsupporting
confidence: 91%
“…Individual investors often use recognition-based heuristics when trading in the stock market; they reduce the mental effort in the decision-making process, but that leads to errors in judgment and, as a result, anomalies persist in the market; due to these anomalies, investors make irrational investment decisions, and their investment performance was affected adversely. The findings are consistent with research by Lazuarni (2019) who found that heuristic biases are reasons for the existence of the technical and fundamental anomalies in the stock market, which negatively affect the investment performance of investors.…”
Section: Discussionsupporting
confidence: 91%
“…Anchoring bias, a cognitive bias that impacts decision-making, plays a crucial role in human behavior [48]. The simplifying behavior of information can impact the occurrence of anomalies in the capital market, and these anomalies may not always negatively affect investment performance [49]. The correlation between the proximity of stock prices to their 52week high and PEAD diminishes when stocks have a high proportion of foreign investor ownership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A person's propensity to depend on knowledge that is already available is known as the availability cognitive heuristic. Decision-making, especially under uncertainty, is carried out through availability heuristics because the experience is inherent in the memory of the decision-maker (Lazuarni and Asri 2019). It concentrates on retrieving information from memory.…”
Section: Availability Heuristicmentioning
confidence: 99%